Tax evasion and tax fraud in the bankruptcy process: empirical evidence from Portugal - Dinis, Ana (2015)
This article aims to analyze the taxation of insolvent companies and how this process can lead to more tax evasion and tax fraud, in Portugal. Thus, this paper intends to explore how the complexity of the tax system allows tax evasion and tax fraud in insolvency proceedings. This paper is divided in two parts. At first, a review of major studies in national and international context, analyze and debate the issues raised by taxation of insolvent companies from the perspective of tax evasion and fraud. In this regard, the complexity of business insolvency, which becomes even more controversial when embra cing the taxation of insolvent companies. Many of the problems that arise for the correct identification of the tax treatment applicable to processes happen to set between tax law and bankruptcy law. Second, we present the results of a study conducted in Portugal in 2013, which qualitatively assesses the perceptions of the Insolvency Administrators (AI), in relation to the taxation of insolvent companies. The technique used for gathering information was the use of questionnaires administered to the entire population of AI. A res ponse rate of 15.48% was obtained. It was concluded that the Portuguese tax system do not make taxation of insolvent companies a clear process, raising many questions about the subject of insolvent companies to tax. Further more, the CIRE by giving primacy to the insolvency, for the sake of business recovery, leads to the possibility of tax evasion and fraud. To sum up, it is dee med indispensable the harmonization of procedures, legal and tax, the CIRE and the CIRC in order to a more consistent treatment of tax in insolvency proceedings, in order to annul the tax evasion and tax fraud case insolvency and also allow business recovery.